An Experience in Tertiary Care Unit: Comparison between Efficacy of Caffeine Versus Aminophylline in Apnea of Prematurity - Afsheen Batool Raza, Ameez Zulfiqar, Nadia Nawaz (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To compare the efficacy of caffeine versus aminophylline in the treatment of Apnea of Prematurity amongst neonates in tertiary care unit. Methods: The comparative cross-sectional research was conducted at Pediatric neonatology unit of The Children’s Hospital & UCHS Lahore from October, 2020 to October, 2021. A total of 60 premature newborn babies fulfilling the selection criteria were enrolled after taking written informed consent from parents and were randomly divided into two groups of equal number i.e. 30 each. Non-Probability Consecutive Sampling. One group received intravenous aminophylline and the other group received intravenous caffeine when first episode of apnea was observed on clinical parameters. Patients were followed for up to 10 days during admission and efficacy was assessed. Results: The mean gestational age of the premature newborn babies in aminophylline versus caffeine group was 29 1.51 versus 30 1.84 weeks. Efficacy of caffeine versus aminophylline was 87% versus 63% (p=0.037), need of oxygen was in 27% versus 57% (p=0.018), need of ventilation was 3% versus 17% (p=0.085), rate of complications was 16% versus 30% (p=0.819) and rate of mortality was 3% versus 20% (p=0.044) respectively. Conclusion: In AOP, caffeine was superior in efficacy than aminophylline in terms of reduction in recurrence of apneic spells, oxygen requirement and mortality rates and were similar in efficacy in terms of need of ventilation and side effects. Keywords: Apnea of prematurity, Efficacy, Caffeine, aminophylline